Semantic Approach on Toshihiko Izutsu’s Translation of Surah Al-Alaq (96:1-19): Comparison of 3 Qur'an in Japanese Translation - Alpina Pamugari (IZUMI, 2021)
Toshihiko Izutsu is a japanese non-Muslim Islamic thinker. He translated the Qur'an into Japanese in a distinctive and striking style compared to any other Japanese translator ever. The study took one example of a letter in the Qur'an, Alaq (96:1-19), and compared Izutsu's Japanese translation with a translation by the Japan Muslim Association (JMA) and Makoto Mizutani. It can be said that the Izutsu version attempts to convey not only the complex layered meaning of each chapter and each section of the Quran, but also the atmosphere of the Quran and the Arabian Peninsula at that time to Japanese readers at the same time. On the other hand, the other two Japanese translations seem to be attempting verbatim translations that are more faithful to the Arabic original. However, it might be able to be said that the JMA  version emphasizes providing an accurate meaning based on the Sunnah classics annotation by putting a detailed note even at the expense of readability while the Mizutani version is same level with JMA but the Arabic text is not attached and it’s the easiest to read among three version.Keyword: Semantics, Toshihiko Izutsu, Qur’an